Recent Cases on Price Maintenance - Spencer, William H. (Journal of Political Economy, 1922)
The Supreme Court of the United States for reasons good or bad has committed itself to the doctrine that an attempt on the part of a manufacturer to control the resale price of his product by contract is an offense punishable under the Sherman Antitrust Act; that such an attempt is unfair competition within the meaning of the Federal Trade Commission Act and can be prohibited by the Trade Commission; and that the contract itself is, of course, unenforcible and not entitled to the protection of the law. The theory of the Supreme Court underlying this conclusion seems to be that "where commodities have passed into the channels of trade and are owned by dealers," the dealers are privileged to sell them at their own prices; and that the factory having "sold its product at a price satisfactory to itself, the public is entitled to whatever advantage may be derived from competition in the subsequent traffic."'T It is not within the scope of this article to examine the fundamentals underlying the view of the Supreme Court in the Miles case, however unsound the decision may seem. But it should be noted in passing that Justice Holmes, that rare genius of the law, dissented from the conclusion of the court and recent cases indicate that he has not yet been converted to the view of the majority. Taking the conclusion of the Supreme Court in the Miles case as the starting-point and assuming the soundness of the decision, the purpose of this article is to trace the more recent development of the law in the federal courts with respect to price maintenance and particularly to note a curious tangle into which the Supreme Court has apparently wandered. When the Supreme Court outlawed price-maintenance contracts on the score that they suppress competition and are therefore contrary to sound public policy, it was perfectly natural that manufacturers should have immediately resorted to other